Progress in treatment of viral infections in children with acute lymphoblastic leukemia - Maria Moschovi; Maria Adamaki; Spiros A. Vlahopoulos (Frontiers Media S.A., 2016)
In children, the most commonly encountered type of leukemia is acute lymphoblastic leukemia (ALL). An important source of morbidity and mortality in ALL are viral infections. Even though allogeneic transplantations, which are often applied also in ALL, carry a recognized risk for viral infections, there are multiple factors that make ALL patients susceptible to viral infections. The presence of those factors has an influence in the type and severity of infections. Currently available treatment options do not guarantee a positive outcome for every case of viral infection in ALL, without significant side effects. Side effects can have very serious consequences for the ALL patients, which include nephrotoxicity. For this reason a number of strategies for personalized intervention have been already clinically tested, and experimental approaches are being developed. Adoptive immunotherapy, which entails administration of ex vivo grown immune cells to a patient, is a promising approach in general, and for transplant recipients in particular. The ex vivo grown cells are aimed to strengthen the immune response to the virus that has been identified in the patients' blood and tissue samples. Even though many patients with weakened immune system can benefit from progress in novel approaches, a viral infection still poses a very significant risk for many patients. Therefore, preventive measures and supportive care are very important for ALL patients.